Muscle thickness of the pectoralis major and rectus abdominis and level of physical activity in chronic hemodialysis patients - Bueno,Aline Felicio (2017)
Abstract Introduction: Patients on chronic hemodialysis tend to lose lean body mass and have sedentary behavior. Objective: To compare the level of physical activity and the morphology of the muscles pectoralis major and rectus abdominis of patients on hemodialysis with healthy subjects. Methods: We studied 17 patients and 17 healthy individuals. Muscle thickness were evaluated by ultrasound, and the level of physical activity by the International Physical Activity Questionnaire (IPAQ), long version. Results: The patients had lower thicknesses of the pectoralis major (5.92 ± 0.35 mm vs. 8.35 ± 0.62 mm, p < 0.001) and rectus abdominis (0.96 ± 0.10 mm vs. 2 21 ± 0.40 mm, p < 0.001) compared to healthy subjects. Patients were physically less active than healthy individuals: 1502.55(788.19-2513.00) MET-minutes/week vs. 2268.0(1680.0-4490,8) MET-minutes/week (p = 0.006); the weekly caloric expenditure of patients was also lower: 1384.0(480,7-2253.7) kcal/kg/week vs. 1680.0(1677.4-4950.0) kcal/kg/week (p = 0.010). The average time spent sitting per week of the patients was higher than in healthy subjects (394.0 ± 33.1 min/day vs. 293.0 ± 38.6, p = 0.009) as well as the average time spent sitting during weekend (460.0 ± 40.1 vs. 201.0 ± 10.7, p = 0.003). Conclusion: Chronic renal failure patients on hemodialysis have sedentary behavior and lower muscle thickness of the trunk.